De l’écrit à l’écran - Jean-Marc Limoges (Cahiers de Narratologie)
This article seeks to do for narrative voices in cinema what Gérard Genette did for narrative voices in literature 40 years ago: scope out a simple and efficient typology able to account for all known and foreseeable narrative possibilities. This will involve establishing the specificities of narrative voices in cinema (i.e. the possibilities exclusively offered by cinema that could not arise in literature) and then reviewing each inventoried configuration to ascertain if these might not also reveal a number of thematic groupings (i.e. specific types of voices corresponding to specific types of stories).